Risk Factors for Nontuberculous Mycobacteria Infections in Solid Organ Transplant Recipients: A Multinational Case-Control Study. (26th July 2022) - Mejia-Chew, Carlos; Carver, Peggy L; Rutjanawech, Sasinuch; Camargo, Luis F Aranha; Fernandes, Ruan; Belga, Sara; Daniels, Shay-Anne; Müller, Nicolas J; Burkhard, Sara; Theodoropoulos, Nicole M; Postma, Douwe F; van Duijn, Pleun J; et al.
Abstract: Background: Risk factors for nontuberculous mycobacteria (NTM) infections after solid organ transplant (SOT) are not well characterized. Here we aimed to describe these factors. Methods: Retrospective, multinational, 1:2 matched case-control study that included SOT recipients ≥12 years old diagnosed with NTM infection from 1 January 2008 to 31 December 2018. Controls were matched on transplanted organ, NTM treatment center, and post-transplant survival greater than or equal to the time to NTM diagnosis. Logistic regression on matched pairs was used to assess associations between risk factors and NTM infections. Results: Analyses included 85 cases and 169 controls (59% male, 88% White, median age at time of SOT of 54 years [interquartile range IQR 40–62]). NTM infection occurred in kidney (42%), lung (35%), heart and liver (11% each), and pancreas transplant recipients (1%). Median time from transplant to infection was 21.6 months (IQR 5.3–55.2). Most underlying comorbidities were evenly distributed between groups; however, cases were older at the time of NTM diagnosis, more frequently on systemic corticosteroids and had a lower lymphocyte count (all P < .05). In the multivariable model, older age at transplant (adjusted odds ratio [aOR] 1.04; 95 confidence interval [CI], 1.01–1.07), hospital admission within 90 days (aOR, 3.14; 95% CI, 1.41–6.98), receipt of antifungals (aOR, 5.35; 95% CI, 1.7–16.91), and lymphocyte-specific antibodies (aOR, 7.73; 95% CI, 1.07–56.14), were associated with NTM infection. Conclusions: Risk of NTM infection in SOT recipients was associated with older age at SOT, prior hospital admission, receipt of antifungals or lymphocyte-specific antibodies. NTM infection should be considered in SOT patients with these risk factors. Abstract : In this multinational, 1:2 matched case-control study of solid organ transplant (SOT) recipients, older age at transplantation; and hospital admission, receipt of antifungals or lymphocyte-specific antibodies within 90 days of nontuberculous mycobacteria (NTM) disease were associated with increased odds of disease in the multivariable model.